Mine shoring with reinforced wood - Toledo Garay, Fernando Enrique (1998)
At present, shoring in a mine with wood continues to be an economic alternative; despite its age and competence with a diversity of elements and materials. This research work consists of looking for the best arrangement for the assembly of construction steel rods in the stress zone of a beam, in order that the steel takes all the stress stresses (fs), and the wood all compression efforts (fw), generated by a concentrated load (in the laboratory). The idea is to make wood and steel work, bonding them intimately with epoxy resins, in order to obtain similar results to that of a reinforced concrete beam. The advantage that wood has over concrete is its low specific weight, which constitutes an important parameter for workability in the subsoil. The economic and time constraints allowed testing only 150 specimens, which were not enough to achieve the desired success. However, it has given us important guidelines, Professors of the Academic Department of Mining Engineering to achieve higher levels of resistance in practice, or in future trials. In the sample No. 113-TOR-11 T (3/8) -AQ / MP, 83% was achieved in increasing its resistance in the elastic limit, with a load of 2,220 Kg., Compared to 1,210 Kg bearing without metal reinforcement.